KELAYAKAN TEORITIS LEMBAR KERJA SISWA GROUP INVESTIGATION MATERI EKOSISTEM UNTUK SMA - MAGHFIROH, NURIL (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
Student Worksheets of Group Investigation help students to solve the problems they found in learning. This research aimed to produce Ecosystem Student Worksheets which are theoretically feasible. Theoretical feasibility was got from worksheets validity by Biology lecturers and teacher. The validation worksheets aspects are presentation, language and readability, conformance with Group Investigation method, conformance worksheets content with Ecosystem concept, and conformance worksheets content with learning objectives. This development research used 4-D model which consists of four phases. The average score of validation worksheets are 3,47 and get very feasible category that they are feasible to be applyed in learning. Keywords: worksheets, Group Investigation, Ecosystem